2011
DOI: 10.1176/appi.neuropsych.23.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Binge Eating in Parkinson's Disease: Prevalence, Correlates and the Contribution of Deep Brain Stimulation

Abstract: Of 96 Parkinson's disease (PD) patients at the University of Florida Movement Disorders Center, one (1%) met diagnostic criteria for binge eating disorder (BED). Eight (8.3%) exhibited subthreshold BED. Psychometric criteria classified problem gambling in 17.8%, hoarding in 8.3%, buying in 11.5%, hypersexuality in 1.0%, and mania in 1.0% of patients. More overeaters met psychometric criteria for at least one additional impulse control disorder (67% vs. 29%). No more overeaters than non-overeaters were taking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 34 publications
2
53
0
Order By: Relevance
“…Moreover, while in men gain seems principally due to an increase in lean mass, in women it is essentially due to fat mass (Montaurier et al, 2007). For what concerns impulsive eating after DBS, Zahodne et al (2011) identified a history of subthalamic nucleus DBS surgery in a sample of 96 PD patients as the only significant predictor of binge-eating, and a trend for an association between subthalamic nucleus DBS and being an overeater. However, as the authors did not compare binge eating before and after surgery, it cannot be concluded that DBS induced binge eating in these patients.…”
Section: Weight Food Intake and Deep Brain Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, while in men gain seems principally due to an increase in lean mass, in women it is essentially due to fat mass (Montaurier et al, 2007). For what concerns impulsive eating after DBS, Zahodne et al (2011) identified a history of subthalamic nucleus DBS surgery in a sample of 96 PD patients as the only significant predictor of binge-eating, and a trend for an association between subthalamic nucleus DBS and being an overeater. However, as the authors did not compare binge eating before and after surgery, it cannot be concluded that DBS induced binge eating in these patients.…”
Section: Weight Food Intake and Deep Brain Stimulationmentioning
confidence: 99%
“…Vitale et al (2011) described 12 patients with compulsive eating, 11 of whom developed this condition after the diagnosis, while one had a history of pathological eating that worsened after the DA therapy. Zahodne et al (2011) evaluated binge eating, as defined by the DSM-IV, in 98 patients with PD and found that, on the Eating Disorder Diagnostic Scale, one of them met full diagnostic criteria for Binge Eating Disorder BED (1%), while additional eight patients (8.3%) exhibited subthreshold binge eating. Both PD patients with and without Deep Brain Stimulation (DBS) were included in this sample.…”
Section: Introductionmentioning
confidence: 99%
“…Time consumed by sexual fantasies, urges or behaviors repetitively interferes with other important (nonsexual) goals, activities and obligations Repetitively engaging in sexual fantasies, urges or behaviors in response to dysphoric mood states Repetitively engaging in sexual fantasies, urges or behaviors in response to stressful life events Repetitive but unsuccessful efforts to control or significantly reduce these sexual fantasies, urges or behaviors Repetitively engaging in sexual behaviors while disregarding the risk for physical or emotional harm to self or others There is clinically significant personal distress or impairment in social, occupational or other important areas of functioning associated with the frequency and intensity of these sexual fantasies, urges or behaviors These sexual fantasies, urges or behaviors are not due to the direct physiological effect of an exogenous substance such as a drug of abuse or medication Abnormal behaviors are different from previous behavior and include excessive masturbation, using pornography, sexual behavior with consenting adults, cybersex, telephone sex, strip clubs, use of sex trade workers Initial studies of ICDs in PD [Pontone et al 2006;Weintraub et al 2006;Grosset et al 2011;Isaias et al 2008;Singh et al 2007;Voon et al 2006] reported a prevalence of 2.2-28.0% for PG [Weintraub et al 2006;Isaias et al 2008], 2.0-11.0% for HS Singh et al 2007], 0.4-6.4% for CS Weintraub et al 2009] and 1-4.5% for CE [Zahodne et al 2011;Weintraub et al 2009]. It is important to recognize that these estimates were obtained with heterogeneous study designs, sample sizes, diagnostic criteria and ascertainment methods.…”
Section: Hypersexuality [Voon Et Al 2006]mentioning
confidence: 99%
“…The prevalence of obsessive eating or binge-eating among patients with PD was 1% in a recent analysis while subthreshold binge eating was diagnosed in about 8% (Zahodne et al, 2011). However, in a cross-sectional study with 3000 patients with PD binge eating was diagnosed in 5.6% (Antonini & Cilia, 2009).…”
Section: Obsessive Eatingmentioning
confidence: 95%